Diagnóstico de la existencia y uso de la maquinaria agrícola en el cantón Montalvo, provincia de Los Ríos - Fernández Morocho, Luiggy Stepen (2024)
For this research, the agricultural production units (UPA) with short cycle (transitional) crops of the Montalvo canton and surrounding parishes will be taken into account as the population. To determine the number of samples, the information obtained directly by direct communication was used. In the MAGAP- Babahoyo offices, where they estimate 1,250 producers. The conclusions determine that in the Montalvo canton, province of Los Ríos, it is composed of farmers who are largely male with 79% and 21% female, the majority with a high school academic level (53%); most farmers have their own land to be able to plant their crops. Farmers consider the use of machinery for their agricultural exploitation to be very important, generally using it for more than 10 years; the majority of producers rent or lease the machinery for the agricultural exploitation, without receiving any advice, using tractor, combine, fumigator (boom), harrow, and seeder. The tractor with a power of 100 to 110 hp and the combine with 100 and/or 110 hp, are the most used in the town; producers pay off the tractor at cost/block: $20; harvester cost / sack or qq: 1.00 to 3 $; fumigator cost/block: $10; harrow cost / block pass: $20; fertilizer spreader cost/block $10; motor pump cost/day: 15$; rice seeder cost / block: 10 - 30$ and corn seeder cost / block: 30 to 45$, emphasizing that the majority of farmers are satisfied with the payment of the cost/hour of renting the machinery and the farmers indicate that it is normal the degree of difficulty in renting agricultural machinery in the area, 100% of them indicating that the machinery used is used – in poor technical condition – but with working capacity.